Contribution of Cyber Literature by Agus Noor to the Preparation of “Kisah - Kisah Kecil dan Ganjil Malam 1001 Pandemi” - Muhammad Afnani Alfian; Ifit Novita Sari (LPPM Stikosa - AWS, 2022)
Cyber literature is literature that is present due to the development of communication media, especially internet media. His presence became a benefit for several writers, including Agus Noor. Agus Noor developed a story idea with flash fiction or a collection of stories taken from Instagram with the use of the hashtag 1001night pandemic. The collection of stories is then combined into a whole story that is recorded. This work is closely related between the cyber world and the literary space to produce a literary work. This research aims to map the work of Agus Noor on social media in relatively deep. The approach used in this study is qualitatively exploratory. With reading without data, but focus on exploration found on Instagram accounts and books. This research will produce some narrative. First, the relationship of cyber literature with the book collection of stories by Agus Noor. Second, the usefulness of cyber literature in making story ideas and stories by Agus Noor.